Portfolio building activities in social media exercises in strategic communication - Freberg, Karen June (SAGE, 2022)
"Portfolio Building Activities in Social Media features over 125 real-world activities across various social media platforms designed to help students engage with social media from the perspective of a professional, strategic communicator. These activities and assignments give students hands-on experiences with real world challenges, and can be used to build a portfolio of work for use with job applications. Designed to be used with Freberg's social media book but flexible enough to bundle with any PR textbook, the exercise guide includes everything from brand analyses to budget assignments to pitch activities"--